Application of nanocatalyst iron oxide (Fe2O3) to reduce exhaust emissions (CO and HC) - Puspitasari P.; Yazirin C.; Bachtiar L.A.; Dika J.W.; Zaharis S.M.S.N.S. (Institute of Physics Publishing, 2024)
Indexed by Scopus